2021
DOI: 10.1080/13880209.2021.1944222
|View full text |Cite|
|
Sign up to set email alerts
|

Antidepressant effects of total iridoids of Valeriana jatamansi via the intestinal flora-blood–brain barrier pathway

Abstract: Context: Valeriana jatamansi Jones [syn. V. wallichii DC, (Valerianaceae)] (VJJ) is used to treat depression. Objective: To explore the effects of total iridoids of VJJ extract (TIV) on chronic unpredictable mild stress (CUMS) in mice. Materials and methods: VJJ roots and rhizomes were extracted with 70% ethanol. CUMS rats were treated daily with fluoxetine (2.6 mg/kg, i.g.) or TIV (5.7, 11.4, and 22.8 mg/kg, i.g.) for 14 days. Male Kun Ming mice on normal chow and 0.5% CMC-Na solution were used as a control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…For CNS, studies have corroborated that VJJ modulates the hypothalamic–pituitary–adrenal axis ( Yan et al, 2010 ; Shi et al, 2014 ), inhibit microglia activation ( Yang et al, 2022 ), and protect the blood–brain barrier ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ). Contrary to the findings of this study, VJJ has been previously demonstrated to inhibit rotavirus-induced diarrhoea by suppressing the PI3K/AKT signalling pathway ( Zhang et al, 2021 ), and 11-Ethoxyviburtinal, derived from VJJ, exerts anxiolytic effects through this pathway’s inhibition ( Lyu et al, 2023 ). These variations may stem from the distinct molecular mechanisms underlying various disorders and the diverse bioactive constituents present in VJJ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For CNS, studies have corroborated that VJJ modulates the hypothalamic–pituitary–adrenal axis ( Yan et al, 2010 ; Shi et al, 2014 ), inhibit microglia activation ( Yang et al, 2022 ), and protect the blood–brain barrier ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ). Contrary to the findings of this study, VJJ has been previously demonstrated to inhibit rotavirus-induced diarrhoea by suppressing the PI3K/AKT signalling pathway ( Zhang et al, 2021 ), and 11-Ethoxyviburtinal, derived from VJJ, exerts anxiolytic effects through this pathway’s inhibition ( Lyu et al, 2023 ). These variations may stem from the distinct molecular mechanisms underlying various disorders and the diverse bioactive constituents present in VJJ.…”
Section: Discussionmentioning
confidence: 99%
“…Employed as an adjunctive therapy, TCM has shown to be advantageous in enhancing motor and sensory functions, as well as the daily living capabilities of individuals with SCI ( Zheng et al, 2020 ). VJJ, with its extensive historical application in TCM, exhibits a wide spectrum of biological activities, including sedative-hypnotic ( Sah et al, 2010 ), antianxiety and antidepressant ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ), anti-tumour properties ( Tian et al, 2020 ). For CNS, studies have corroborated that VJJ modulates the hypothalamic–pituitary–adrenal axis ( Yan et al, 2010 ; Shi et al, 2014 ), inhibit microglia activation ( Yang et al, 2022 ), and protect the blood–brain barrier ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection, gastrointestinal bleeding, and pulmonary embolism, significantly increasing mortality. [4] Valeriana jatamansi Jones (VJJ), also known as Zhi zhu xiang, an oral Chinese herbal medicine with a long history of use, has a variety of biological functions, including sedativehypnotic, [5] antianxiety, antidepressant, [6] antibacterial, antiviral, [7] and antitumor [8] effects, without obvious signs of drug dependence or toxic effects. [9,10] VJJ is a Chinese herbal medicine with promising future development.…”
Section: This Work Was Supported By Special Research Project Of Tradi...mentioning
confidence: 99%
“…In addition, administration of TIV for 2 weeks in CUMS adult male KM mice could also elevate the expression of zonula occludens-1 (ZO-1) and occludin to reduce the BBB permeability and balance the relative abundance of firmicutes and bacteroidetes (Zhang L et al. 2021 ). According to a comprehensive serum metabolomics study using NMR, TIV may exert antidepressant effects through various metabolic pathways, including neurotransmitter synthesis, tricarboxylic acid cycle regulation, and amino acid metabolism (Li, Wu, et al.…”
Section: Iridoids In Treatment Of Depressionmentioning
confidence: 99%